Implementasi Teori Manajemen dalam Kegiatan 17 Agustusan di Desa Lubuk Resam dalam Perspektif Kuliah Kerja Nyata (KKN) - Revaldo, Ardian; Arianto, Tezar; Nengsih, Mimi Kurnia (Jurnal Dehasen Untuk Negeri, 2025)
The community service programme (KKN) in Lubuk Resam Village aims to implement management theory in the organisation of the 17 Agustusan event, an important annual celebration for the local community. In this activity, students had to apply various management functions, such as planning and organising. As well as having to communicate and report the results of company activities, information, personnel tasks both orally and in writing, and directing and controlling to ensure the event runs smoothly. The planning process includes setting activity objectives, developing a schedule, and allocating a budget. Organising is done by forming a committee that divides specific tasks to manage various aspects of the event. Directing involves coordination between committee members and the community to ensure that each component of the activity goes according to plan. Controlling is done through periodic evaluations to assess the effectiveness and impact of the activities. This article reviews how KKN students play an active role in supporting activities and assisting village communities through the application of theoretical and practical approaches. The results of the activities showed that the application of management theory effectively improved the smooth running of the events and motivated active participation from the villagers. With a systematic managerial approach, the 17 Agustusan activities in Lubuk Resam Village were able to run in a more structured manner, facilitating social interaction and strengthening community spirit. These findings suggest that the application of management theory not only improves the efficiency of activities but also provides significant benefits for the development of village communities.